Urodynamics in patients with multiple sclerosis: is it necessary? A randomized-controlled trial. (4th March 2021) - El Helou, Elie; Sarkis, Julien; Mjaess, Georges; Zalaket, Jad; Mouawad, Christian; Sayegh, Nicolas; Ghattas, Souad; Azar, Carine; El Helou, Jeanine; Abboud, Halim; Koussa, Salam; Nemr, Elie
Abstract: Background: The need for complete urodynamic evaluation in Multiple Sclerosis (MS) patients with Lower Urinary Tract Symptoms (LUTS) is not fully established in the literature. The objective was to evaluate the effect of urodynamics in MS patients with LUTS on treatment outcomes. Methods: MS patients with LUTS were recruited. On their first visit, urinary symptoms, symptom bother and urologic quality-of-life were evaluated using standardized questionnaires. On their second visit, patients were randomized into two groups: Group A underwent uroflowmetry, and Group B underwent a urodynamic study. Patients received treatment based on the whole evaluation and then were evaluated at 1, 3 and 6 months. Results: Fifty MS patients with LUTS were randomized to 25 patients in each group. All scores decreased significantly after 6 months of treatment in both groups ( p  < 0.05). However, no differences were found between the two groups at baseline and at 1, 3 and 6 months of treatment ( p  > 0.05) concerning treatment outcomes. Conclusion: A detailed clinical and non-invasive evaluation of MS patients with LUTS seems to be sufficient for prescribing an effective treatment. A urodynamic study does not influence the response to the prescribed treatment in terms of LUTS severity, bother or urologic quality-of-life.